Depth distribution of the velvet belly, Etmopterus spinax, in relation to growth and reproductive cycle: the case study of a deep-water lantern shark with a wide-ranging critical habitat - Coelho, Rui (2017)
The velvet belly lantern shark, Etmopterus spinax (Squaliformes: Etmopteridae), is a small-sized squalid shark commonly found in deep waters off the Portuguese coast, mainly on soft bottoms. In this study, 67 research cruise bottom trawl tows (with 1-hour duration) were carried out at depths that ranged from 84 to 786 m. A total of 396 specimens (192 males and 204 females) were caught, with total lengths and ages ranging, respectively, from 10.2 to 32.9 cm and 0 to 7 years for males and from 9.8 to 41.1 cm and 0 to 10 years for females. Size, age, sex and maturity stages were found to be correlated with depth, with the larger, older and mostly mature specimens occurring predominantly at greater depths. There seems to be a depth-related migration, where the pregnant females migrate from deeper mating grounds to shallower nursery grounds. The sex ratios were relatively similar in the shallower strata, but females dominated at more than 600 m and were exclusive at more than 700 m. Fishing-related mortality may have complex and significant repercussions on this species, given that commercial fisheries are impacting different segments of this population differently.